Liver Cancer Mortality Rates in Peru: Trend Analysis from 2003 to 2017 - Torres Roman, J. Smith (2025)
Background: Liver cancer is one of the leading causes of cancer-related death in Peru, and some reports have indicated an increase in mortality rates among the largest cities. To our knowledge, no study has been carried out at a national level or by geographic area in recent years. Thus, our objective was to examine overall, regional and sexspecific liver cancer mortality rates in Peru between 2003-2017. Methods: We retrieved data on liver cancer deaths between 2003 and 2017 from the mortality database of the Peruvian Ministry of Health. Age-standardized mortality rates (ASMR) were estimated per 100,000 person-years using the world standard SEGI population. We analyzed mortality trends using Joinpoint regression Program Version 4.7.0. To examine the spatial distribution of the mortality rates, we used GeoDa software. Results: Between 2003 and 2017, 31,473 deaths from liver cancer were reported in Peru. Overall, liver cancer mortality rates have decreased significantly among Peruvian women since 2005 (−3.1% annually) with decreases in the coastal and highland regions ranging from 2.8% to 3.5%. In Arequipa, Cusco, La Libertad, Lima, and Moquegua, rates decreased bewteen 2003 and 2017. Among men in Ancash a significant increase (+12.5 annually) was observed from 2003-2011, followed by a sharpdecline (−10.5 annually) between 2011 and 2017. In contrast, rates in Cajamarca, Junin, and Ucayali decreased between 2003 and 2017. Conclusions: Although decreases in liver cancer mortality rates were observed in some regions of Peru, these trends were not statistically significant. In addition, some provinces experienced increases in rates. Effective interventions, such as expanding access to healthcare and controlling the various risk factors for liver cancer, remains a key challenge for the country.